Implementasi Nilai-Nilai Pendidikan Islam Dalam Kegiatan Infaq Jumat di Smpit Al-Arabi Cikarang - Hanif, Ayasis Aulia; Sitika, Achmad Junaedi; Nurhasan, Nurhasan (Jurnal Ilmiah Wahana Pendidikan, 2025)
This thesis is the result of the author's research how teachers use infaq activities to implement the values ​​of Islamic education. Infaq activities are practices that can be carried out in everyday life and become a link in a learning process by leading, giving an example and supervising so as to produce a generation of morals that can be applied in wider society. Instilling Islamic beliefs in schools is very important because every individual can easily change. Instilling Islamic beliefs in schools is essential to complement non-family education and ensure its consistent implementation. Data for this paper were gathered utilizing a qualitative strategy, a literature review method, and a field research approach. Where data is gathered through observation, interviews, and documentation. The goal is to analyze, research, find, describe, and explain the properties or characteristics of unexplained social influences. The study found that including Islamic education values into infaq activities positively impacts children's character and social caring, particularly at SMPIT Al-Arabi Cikarang.